PENGEMBANGAN MEDIA VIDEO ANIMASI BERBASIS POWTOON TERHADAP KEPERCAYAAN DIRI SISWA KELAS VIII MTS AL QODIRIYAH - Sandiani, Sonia; Rukanda , Nandang; Alawiyah, Tuti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2023)
This research aimed to discover the appropriateness of powtoon-based animation videomedia on the MTS Alqodiriyah students’ confidence, who are in adolescence accordingtotheirage;thiseraiscrucialfortheteenagerstodeveloptheirconfidence.The research and development technique was employed in this study (RnD). The participants in this study were 7 eighth-grade MTS Alqodiriyah students. The validity product test was conducted byproduct experts, material experts, school practitioners, and students’ responses on thepowtoon-basedanimationvideomedia.The research's findings indicated that the creation of animated video media based on Powtoon obtained 96% of the results indicating that the product is appropriate and falls under the proper category, making it useful for the implementation of guidance and counseling services.